PREFERENSI PEMILIK SWALAYAN TERHADAP PENGADAAN PRODUK MAKANAN BERLABEL HALAL (Studi Kasus di Kota Banda Aceh) - Teuku Muhammad Syahrizal (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2019)
The research aims to know (1) The influence of prices, products, halal and religious labels against the preference of self-service owners on packaged food products and (2) see if the Halal label becomes a major factor or not in influencing preference. This research is a quantitative study. The population of research is a self-service owner in Banda ACEH that has business licenses. The sampling is a self-service owner of Islam and has a business license in the year 2015-2016, from that year net of 16 supermarkets used as sample. Data collection techniques using questionnaires. Analytical techniques use classical assumption tests (test normality, multicolinearity, heteroskedastisity and multiple regression) using SPSS version 20. The results showed: (1) product (X1), Price (X2), halal label (X3) and religious (X4) have a significant influence on the preference of self-service owner. Each variable has a significance value (p) of < 0.05, where the significance values are X: 0.019, X2:0.017, X3:0.011 and X4:0.037. The factors together indicate significance to the preference with a significance value of 0.000 (sig. 0.000 < 0.05). (2) Halal Label is not a major factor that affects the preference of self-service owner. So the main factor is the product with a value of Î²: 0.358.